2018
DOI: 10.1038/s41438-018-0073-7
|View full text |Cite
|
Sign up to set email alerts
|

Tomato DCL2b is required for the biosynthesis of 22-nt small RNAs, the resulting secondary siRNAs, and the host defense against ToMV

Abstract: The tomato encode four functional DCL families, of which DCL2 is poorly studied. Here, we generated loss-of-function mutants for a tomato DCL2 gene, dcl2b, and we identified its major role in defending against tomato mosaic virus in relation to both natural and manual infections. Genome-wide small RNA expression profiling revealed that DCL2b was required for the processing 22-nt small RNAs, including a few species of miRNAs. Interestingly, these DCL2b-dependent 22-nt miRNAs functioned similarly to the DCL1-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 49 publications
2
39
0
Order By: Relevance
“…Further research of non-model plants is needed to characterize components of the RNAi machinery and their roles in biogenesis and function of viral siRNAs. This research will certainly be facilitated by CRISPR-based gene editing technology, as for example recently implemented in tomato to reveal the role of one of the four paralogs of DCL2 in 22-nt siRNA biogenesis and antiviral defense ( Wang T. et al, 2018 ). As mentioned above, combination of small RNA sequencing with direct sequencing of long RNA and DNA molecules using PacBio and Nanopore technologies should enable reconstruction of complete viral genomes and discovery of their mutant and recombinant variants in mixed virome quasispecies.…”
Section: Concluding Remarks and Outlookmentioning
confidence: 99%
“…Further research of non-model plants is needed to characterize components of the RNAi machinery and their roles in biogenesis and function of viral siRNAs. This research will certainly be facilitated by CRISPR-based gene editing technology, as for example recently implemented in tomato to reveal the role of one of the four paralogs of DCL2 in 22-nt siRNA biogenesis and antiviral defense ( Wang T. et al, 2018 ). As mentioned above, combination of small RNA sequencing with direct sequencing of long RNA and DNA molecules using PacBio and Nanopore technologies should enable reconstruction of complete viral genomes and discovery of their mutant and recombinant variants in mixed virome quasispecies.…”
Section: Concluding Remarks and Outlookmentioning
confidence: 99%
“…Recently, the DCL2b-dependent miRNA pathway in tomato was shown to affect susceptibility to PVX and TMV [43]. DCL2b is also required for the biosynthesis of 22-nt small RNAs to defend against ToMV [44].…”
Section: Discussionmentioning
confidence: 99%
“…The values with the double asterisk (**p < 0.01) and single asterisk (*p < 0.05) were statistically significant at the 1% and 5% levels, respectively, compared with those of healthy empty vector-transformed plants biogenesis. We recently showed a defect in the biogenesis of siRNAs, especially 22 nt siRNAs, derived from viroid RNA in hpDCL2.4 plants infected with the potato spindle tuber viroid [44]. Studies have reported the increased accumulation of CMV genomic RNAs [12] and increased susceptibility to PVX and the TuMV helper componentprotease mutant in Arabidopsis DCL double (DCL2 and 4) and triple mutants (DCL2, 3, and 4) [56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CRISPR-Cas9 technology has also been used to knock out crucial genes involved in resistance pathways, aiming to test whether these genes can confer immunity against viruses. Tomato Dicer-like 2 ( DCL2 ) genes were targeted, and the dcl2 mutants displayed viral symptoms when infected by potato virus X, tobacco mosaic virus, and tomato mosaic virus, suggesting that DCL2 is involved in the defense mechanism against RNA viruses 84,85 .…”
Section: Applications Of Crispr-cas9 In Fruit Cropsmentioning
confidence: 99%